Income Contribution of Housewives as Workers in the Ant Palm Sugar Industry Kontribusi Pendapatan Ibu Rumah Tangga Sebagai Pekerja Industri Gula Semut Sari Aren - Sulistiawati, Mayasari (Agribusiness and Socioeconomic Journal, 2023)
Income Contribution of Housewives as Workers in the Ant Sari Palm Sugar Industry in Rejang Lebong Regency, aims to find out the family income of housewives as workers in the Ant Sari Palm Sugar Industry and to find out how much the contribution of housewives as workers in the Ant Sugar Industry palm juice. This research was carried out in July 2023 in Air Meles Atas Village, Selupu Rejang District, with the consideration that there had been no previous research in this area regarding "Income Contribution of Housewives as Workers in the Semut Sari Aren Sugar Industry". The conclusion that can be drawn from this research is that the average total income of female employees of palm sugar palm sugar employees in Air Meles Atas Village, Selupu Rejang District, Rejang Lebong Regency is IDR. 4,800,000,- per month with an average of Rp. 1,200,000,- per month and the daily wage is Rp. 60,000,-. And family income/side income of Rp. 3,500,000,- per month and the average is Rp. 875,000,-. With a total family income of Rp. 8,300,000,-. The income contribution of female employees of sugar palm sugar ant cider was obtained at 57.83%. The contribution value has shown to be quite high, meaning that women who work as employees of palm sugar ant cider have helped meet the family's needs.    Keywords: Contribution, Ant Sugar, IRT